Disgust propensity has a causal link to the stigmatization of people with cancer - Azlan, Haffiezhah An-Nadiah; Overton, Paul Geoffrey; Simpson, Jane; Powell, Philip A. (Springer, 2020)
Disgust-driven stigma may be motivated by an assumption that a stigmatized target presents a disease threat, even in the absence of objective proof. Accordingly, even non-contagious diseases, such as cancer, can become stigmatized by eliciting disgust. This study had two parts: a survey (n = 272), assessing the association between disgust traits and cancer stigma; and an experiment, in which participants were exposed to a cancer surgery (n = 73) or neutral video (n = 68), in order to test a causal mechanism for the abovementioned association. Having a higher proneness to disgust was associated with an increased tendency to stigmatize people with cancer. Further, a significant causal pathway was observed between disgust propensity and awkwardness- and avoidance-based cancer stigma via elevated disgust following cancer surgery exposure. In contrast, those exposed to cancer surgery not experiencing elevated disgust reported less stigma than controls. Exposure-based interventions, which do not elicit disgust, may be profitable in reducing cancer stigma